2020
DOI: 10.3847/1538-4357/abb887
|View full text |Cite
|
Sign up to set email alerts
|

Intercycle and Intracycle Variation of Halo CME Rate Obtained from SOHO/LASCO Observations

Abstract: We report on the properties of halo coronal mass ejections (HCMEs) in solar cycles 23 and 24. We compare the HCME properties between the corresponding phases (rise, maximum, and declining) in cycles 23 and 24 and compare those between the whole cycles. Despite the significant decline in the sunspot number (SSN) in cycle 24, which dropped by 46% with respect to cycle 23, the abundance of HCMEs is similar in the two cycles. The HCME rate per SSN is 44% higher in cycle 24. In the maximum phase, cycle 24 rate norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…All of them were marked as "poor" events, and for many of them estimating associated mass and kinetic energy was impossible. No halo-CME was observed during this period (Dagnew et al, 2020). Thus the number of events in our simulation ( 19) appears comparable with the number of recorded CMEs.…”
Section: Concluding Discussionsupporting
confidence: 74%
“…All of them were marked as "poor" events, and for many of them estimating associated mass and kinetic energy was impossible. No halo-CME was observed during this period (Dagnew et al, 2020). Thus the number of events in our simulation ( 19) appears comparable with the number of recorded CMEs.…”
Section: Concluding Discussionsupporting
confidence: 74%
“…However, CMEs vary in their occurrence rate as well as in their characteristics over different solar cycles. While flare rates and their properties have not changed much over the past solar cycles, the CME properties for solar cycle 24 are significantly different as given in recent statistics (Lamy et al 2019;Dagnew et al 2020b). CMEs were found to be more numerous Fig.…”
Section: General Characteristicsmentioning
confidence: 97%
“…It can be found that the two periods, 1.3 years and 1.7 years, are mainly focused on the parameters of various types of solar radiation and plasma in an interplanetary environment, which are usually considered to be related to the energy released from the Sun. Therefore, it may suggest the important role of halo CMEs in the interplanetary environment and space weather (Gopalswamy et al 2015;Dagnew et al 2020).…”
Section: Discussionmentioning
confidence: 99%